2017
DOI: 10.1016/j.celrep.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Non-Canonical Hedgehog Signaling Is a Positive Regulator of the WNT Pathway and Is Required for the Survival of Colon Cancer Stem Cells

Abstract: Colon cancer is a heterogeneous tumor driven by a subpopulation of cancer stem cells (CSCs). To study CSCs in colon cancer, we used limiting dilution spheroid and serial xenotransplantation assays to functionally define the frequency of CSCs in a panel of patient-derived cancer organoids. These studies demonstrated cancer organoids to be enriched for CSCs, which varied in frequency between tumors. Whole-transcriptome analysis identified WNT and Hedgehog signaling components to be enhanced in CSC-enriched tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
106
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 82 publications
(102 reference statements)
5
106
0
Order By: Relevance
“…407 However, a report showed that noncanonical Hh signaling is a positive regulator of Wnt signaling in colon CSCs. 408 In addition, crosstalk between pathways promotes cell growth and metastasis through maintenance of the CSC population. Downregulation of Notch1 and IKKα enhances NF-κB activation to promote the CD133 + cell population in melanoma CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…407 However, a report showed that noncanonical Hh signaling is a positive regulator of Wnt signaling in colon CSCs. 408 In addition, crosstalk between pathways promotes cell growth and metastasis through maintenance of the CSC population. Downregulation of Notch1 and IKKα enhances NF-κB activation to promote the CD133 + cell population in melanoma CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…As PTCH may mainly function as a cholesterol transporter, it might also affect other signaling pathways. In fact, in recent years SMO-independent PTCH signaling has been reported [11][12][13][14] . However, the mechanistic understanding of these non-canonical Hh signaling pathways remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The small number of CSCs present in primary and xenograft tumor tissue has been a limiting factor in the elucidation of molecular mechanisms regulating CSCs in solid tumors. In our recent study, 2 we used CSC-enriched colon cancer patient-derived organoids (PDOs) to extract CSC subpopulations for molecular and functional characterization. These PDOs demonstrated both functional and molecular inter-and intratumor heterogeneity, with only a fraction of cells within each tumor being tumorigenic.…”
mentioning
confidence: 99%